Curtailment of autoimmunity following parabiosis with a normal partner. - McCullagh, P (1990)
The development of thyroiditis in DA rats that had been exposed to 131I in utero was prevented by parabiosis to normal, syngeneic partners. However, if the normal partner had received sublethal irradiation before parabiosis, thyroid implants placed in either partner were likely to manifest spontaneous thyroiditis.